Meeting breastfeeding intentions differ by race/ethnicity, Infant and Toddler Feeding Practices Study‐2 - Heather C. Hamner; Jennifer L. Beauregard; Ruowei Li; Jennifer M. Nelson; Cria G. Perrine (Wiley, 2021)
Abstract Prenatal breastfeeding intentions impact breastfeeding practices. Racial/ethnic disparities exist in breastfeeding rates; it is unknown if prenatal intentions and meeting intentions differ by race/ethnicity. A longitudinal cohort of USDA's Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) which enrolled participants beginning in 2013 were used to estimate prenatal intentions for breastfeeding initiation, exclusive breast milk feeds at 1 and 3 months by race/ethnicity (n = 2070). Meeting intentions were determined by reported breast milk consumption at birth, 1 month and 3 months. Multivariable logistic regression was used to determine the association of race/ethnicity with meeting intentions. There were no differences in prenatal breastfeeding intentions between non‐Hispanic White and non‐Hispanic Black women (initiation: 86.9% and 87.2%; Month 1: 52.3% and 48.3%; Month 3: 43.8% and 40.9%; respectively), but a higher percentage of Hispanic women intended to breastfeed at all time points (95.5%, 68.3% and 56.4%; respectively, P < 0.05). Among women who intended to breastfeed at Month 1, non‐Hispanic Black and Hispanic women had significantly lower odds of meeting intentions compared with non‐Hispanic White women after adjusting for covariates (aORs: 0.63 [95% CI: 0.41, 0.98]; 0.64 [95% CI: 0.44, 0.92], respectively). Similar findings were seen for Month 3. Despite no differences in breastfeeding intentions, non‐Hispanic Black women were less likely to meet their breastfeeding intentions than non‐Hispanic White women. Hispanic women were more likely to intend to breastfeed yet were less likely to meet their intentions. This suggests that non‐Hispanic Black and Hispanic women face challenges to meeting their longer breastfeeding intentions. Understanding how racism, bias and discrimination contribute to women not meeting their breastfeeding intentions may help efforts to reduce breastfeeding disparities.